Estructuración del sistema para la producción artesanal de vinos en la ciudad de Ambato para la comercialización a nivel nacional - Fabara Camino, Nelly Elizabeth (2011)
Studies show that the project is feasible to produce quality organic wines Ecuador since the country has a strategic sector such as the province of Tungurahua, with basic features for growing vines grape plants about 5000, in 2 hectares of land available later to make the transformation of the raw material by vinification processes based on good manufacturing practices to ensure their quality for consumers, allowing the generation of 6050 bottles of wine per year.